Prolonged elevated postprandial sugar augments severity in kidney disease: a North Indian hospital-based study. (February 2014) - Chandra, Subhash; Singh, Alok K.; Singh, Mritunjai; Das, Parimal; Singh, Shivendra; Pandey, Haushila P.; Singh, Rana G.
Abstract Aim: Diabetes plays a major role in progression of renal failure. The risk-factor profile changes during the progression of chronic kidney disease (CKD) from mild/moderate to end-stage renal disease. The relationship between glycemic indices, blood pressure, body mass index (BMI) and age at diagnosis in Indians has been less investigated. We assessed association of these risk factors with CKD stages in Indian population. Methods: This study was carried out on patients (n = 162) who were diagnosed with CKD and normal control group (n = 155). For BMI, National Institutes for Health criteria were used to categorize the patients. Result: The mean age of CKD patients were significantly increased with the advancement of stage. BMI, systolic blood pressure (SBP), postprandial sugar level (PP), urea and creatinine were also significantly higher with elevated stages, whereas no differences were observed in diastolic blood pressure (DBP) and fasting blood sugar (FBS). The logistic regression study gave a significant result (p = 0.000) when we compared the group of CKD patients with established/prolonged postprandial blood sugar. It was independently associated with mild CKD [odds ratio (OR) = 5.213, 95% confidence interval (CI) = 2.06–13.21, p = 0.000], moderate CKD (OR = 7.724, 95% CI = 4.05–14.74, p = 0.000) and severe CKD (OR = 7.610, 95% CI = 4.03–14.36, p = 0.000). Conclusion: SBP and PP were the best predictors of prevalent nephropathy in this population, while DBP and FBS were found to be less effective. This may have implication for kidney disease risk stratification and protection.